Google Trend Seminggu Pasca Kebijakan Antisipatif dalam Cegah Gagal Ginjal Akut Misterius pada Anak - Rati Purnama Sari; Verra Widhi Astuti; Indri Ramadini; Nurul Aziza Ath Thaariq; Nindy Audia Nadira; Evi Lestari Siaban; Yudistira Afconneri (Jurnal Sehat Mandiri, 2023)
There will be an increase in cases of Acute Kidney Disease (ARF) in children in 2022. As of October 18 2022, 189 cases were found, the majority of which were in children aged 1-5 years. The sudden increase in cases of ARF in children is thought to be related to intoxication of drug syrup containing ethylene glycol (EG) and diethylene glycol (DEG) contaminants. As an anti-addictive measure, the government stipulates a ban on the use of syrup in children.This study aims to obtain information about google trends a week before and after the release of anticipatory policies on efforts to prevent mysterious acute kidney failure in children. Secondary data analysis was carried out using the data reading feature from Google Trends. This search reflects the changing trend of search interest on Google related keywords. Keywords are selected and 5 keywords are taken that show the most searches. The 5 keywords are "acute kidney failure", "syrup medicine", "prohibited drug", "paracetamol" and "prohibited syrup drug". The conclusion is Searches with these keywords are evenly distributed in all regions in Indonesia. The increase in searches based on Google Trends represents the public's interest in accessing health information. Recommended the use of online information media as a media for health information needs attention and the need for literacy education for the public so they can choose the right information.